Magnetorheological Damper Intended for Dissipating Recoil Energy in 12.7 mm Gun - Marcin BAJKOWSKI; Marek RADOMSKI; Zdzisław LINDEMANN (Problemy Mechatroniki)
The paper concerning magnetorheological damper presents the evaluation of the parameters, which provide the required dissipation level of the energy of a recoil effect while shooting series from 12.7 mm gun, and required durability for particular parts of the damper for extreme working conditions. Special damper intended for the controlled arm module ZSMU-A was the subject of the study. The scope of the conducted study is as follows: identification of the maximum value of pressure inside the damper’s chamber, modification of the sealing solution for the damper’s rod, calculation of the strength of the housing and threaded connections.